Electronic Permit to Work (e-PTW) System as an Effort to Control Hot Work Risks and Fire Protection System Safety at PT. XYZ - Didik Mustakim; Nur Rokhman (Rifa'Institute, 2026)
Introduction: This study is motivated by the high risk of fire and safety incidents in large-scale commercial buildings, particularly those arising from Hot Work and Fire Protection Impairment activities that are inadequately controlled through conventional paper-based permit systems. Objective: This study aims to describe the development, implementation, and evaluation of the effectiveness of the Electronic Permit to Work (e-PTW) system for controlling risks associated with Hot Work and Fire Protection Impairment activities at PT. XYZ Building Complex, Jakarta. Method: Using a qualitative approach with a case study design, data were collected through in-depth interviews with stakeholders (HSE, Engineering, Security, and Tenant), observations, document analysis, and a questionnaire to contractors. The e-PTW system was developed using the Jotform platform with features such as forced compliance, sequential workflow, photo evidence upload, automatic notifications, audit trail, and HIRADC risk assessment integration. The system was implemented in stages through socialization, training, pilot testing, and full rollout. Result and Discussion: The findings show that e-PTW successfully reduced risk levels of Hot Work and Fire Protection Impairment from Extreme/High to Medium/Low categories. User satisfaction reached an average score of 4.05 (Effective). The system also improved permitting efficiency, transparency, accountability, inter-divisional coordination, and strengthened the safety culture. Conclusion: Although challenges such as contractor resistance and the need for continuous training persist, this study concludes that e-PTW is an effective digital transformation tool that enhances safety management in large-scale commercial buildings